Fostering sustainable behavior an introduction to community-based social marketing - McKenzie-Mohr, Doug 1959-; Smith, William A. (William Arthur). (Gabriola Island, BC New Society Publishers, 1999)
Fostering Sustainable Behavior An Introduction to Community-Based Social Marketing Doug McKenzie-Mohr and William Smith A sustainable future will require sweeping changes in public behavior. While conventional marketing can help create public awareness, social marketing identifies and overcomes barriers to long-lasting behavior change. This invaluable resource is for anyone involved in designing public education programs with the goal of promoting sustainable behavior, from recycling and energy efficiency, to alternative transportation.
Fostering Sustainable Behavior -- Regulation -- Information -- Changing Attitudes to Influence Behavior -- Promoting Economic Self-Interest -- Community-Based Social Marketing: An Overview -- Uncovering Barriers and Benefits -- Three Steps for Uncovering Barriers and Benefits -- Literature Review -- Conducting a Literature Search -- Qualitative Research -- Observational Studies -- Observational Example: Recycling in a Public Area -- Focus Groups -- Example: What questions matter? -- Survey -- Seven Steps in Creating a Survey -- Some Closing Thoughts -- Commitment: From Good Intentions to Action -- Understanding Commitment -- Commitment and Sustainable Behavior -- Building Commitment into Your Program -- A Checklist for Using Commitment -- Examples: Using Commitment to Foster Sustainable Behavior -- Waste Reduction -- Energy Conservation -- Water Conservation -- Transportation -- Prompts: Remembering to Act Sustainably -- Prompts and Sustainable Behavior -- Prompts and Source Reduction -- Building Prompts into Your Program -- A Checklist for Using Prompts -- Examples: Using Prompts to Foster Sustainable Behavior -- Waste Reduction -- Energy Conservation -- Water Conservation -- Transportation -- Norms: Building Community Support -- Social Norms and Sustainable Behavior -- Using Norms Effectively -- A Checklist for Using Norms -- Examples: Using Norms to Foster Sustainable Behavior -- Waste Reduction -- Energy Conservation -- Water Conservation -- Transportation -- Communication: Creating Effective Messages.
Includes bibliographical references (pages 140-149)
Keywords: Environmental responsibility -- Citizen participation; Environmental responsibility -- United States -- Citizen participation; Community Participation; Conservation of Natural Resources; Social Marketing